Electroacupuncture and Acupuncture Promote the Rat's Transected Median Nerve Regeneration - Ho, C. Y. (Hindawi Publishing Corporation, 2013)
Background. Acupuncture and electroacupuncture treatments of damaged nerves may aid nerve regeneration related to hindlimb function, but the effects on the forelimb-related median nerve were not known. Methods. A gap was made in the median nerve of each rat by suturing the stumps into silicone rubber tubes. The influences of acupuncture and electroacupuncture treatments on transected median nerve regeneration were evaluated from morphological, electrophysiological, and functional angles. Results. Morphologically, the group receiving acupuncture and electroacupuncture treatments had larger total nerve area and blood vessel number compared with the controls. Electrophysiologically, the group receiving electroacupuncture had significantly larger amplitude and larger area of the evoked muscle action potentials compared with the controls. Functionally, the acupuncture and electroacupuncture treatments enhanced the injured paw's ability to regain its grasping power and resulted in a faster efficiency to a new bilateral balance. Conclusion. Our findings provide multiapproach evidence of the efficacy of acupuncture and electroacupuncture treatments to the regeneration of median nerve. Indeed, acupuncture and electroacupuncture appear to have positive effects on the regeneration processes. This platform is beneficial to further study the clinical application of acupuncture and electroacupuncture alternative treatments on nerve-injured patients.